Couple Dynamics in Family Holidays Decision-making Process - Rojas-de-Gracia, María Mercedes; Alarcón-Urbistondo, María del Pilar; González-Robles, Eva María (Emerald Insight, 2018)
-This work addresses two objectives: to identify the roles of the couple at each stage and to determine the most influential variables. To do so, we work with a sample of 375 couples whose members completed a questionnaire separately, which adds reliability to the results. Our results indicate that there are differences between male and female perceptions. In addition, this work reveals that holidays follow a joint decision process in the initiation phase and in the final decision, while the search for information is carried out equally by one of the members of the couple. The woman's employment situation, the type of destination to be travelled to and the difference in educational levels between both are the variables that best explain how couples decide on their family holidays. -Este trabajo aborda dos objetivos: identificar en cada etapa los roles de la pareja y determinar las variables más influyentes. Para ello se trabaja con una muestra de 375 parejas cuyos miembros cumplimentaron un cuestionario por separado, lo que añade fiabilidad a los resultados. Nuestros resultados apuntan a que existen diferencias entre la percepción masculina y femenina. Además, este trabajo revela que las vacaciones siguen un proceso de decisión conjunta en la fase de iniciación y en la decisión final, mientras que la búsqueda de información la realiza por igual uno de los miembros de la pareja. La situación laboral de la mujer, el tipo de destino al que se viaja y la diferencia de niveles educativos entre ambos son las variables que mejor explican cómo las parejas deciden sus vacaciones familiares.
Keywords: Turismo - Toma de decisiones; Familia - Toma de decisiones; Toma de decisiones familiares; Roles de pareja; Vacaciones familiares; Influencia percibida de la pareja; Marketing turístico; Triángulo de viabilidad; Decision-making process; Couple roles; Family holidays; Feasibility triangle; Influence of the couple